Re-Thinking Sustainable Development within Islamic Worldviews: A Systematic Literature Review - Odeh Al-Jayyousi (16937040) (2022)
Many models of economic growth and sustainable development like circular economy, doughnut economy, and sharing economy were articulated to address the global issues including poverty, climate change, and inequity. However, these models were not informed by traditional value-based worldviews. This systematic literature review aims to gain insights on the different models, practices, and drivers for Islamic sustainable development to inform a new discourse for sustainability. Besides, it intends to define emerging themes in sustainable development and explore the viability for adopting Islamic development models to promote inclusive, pro-poor, and human-centred development. The methodology adopted is systematic literature review to identify sustainability models, practices, and drivers in Islam. Policy recommendations and strategic directions are outlined based on the review. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14127300